The F-0 larva of Angelagrion nathaliae Lencioni, 2008 from Southern Minas Gerais state, Brazil (Odonata: Coenagrionidae) - Ferreira, Eike Daniel Fôlha; Oliveira, Tomás Matheus Dias De; Souza, Marcos Magalhães De; Lencioni, Frederico A. A.; Vilela, Diogo Silva (Zootaxa, 2024)
In this study, we described the last instar larva of Angelagrion nathaliae Lencioni, 2008, the first one described for this genus, collected in Inconfidentes and Uberlândia municipalities, Minas Gerais state, Brazil. We compared the diagnostic characters of A. nathaliae with some species of Telebasis Selys, 1865. Despite some similarities with Telebasis larvae, the larva of A. nathaliae can be distinguished from the family by a combination of characters of the mouthparts and gills.